Cyclobenzaprine-related adverse events: a comprehensive pharmacovigilance analysis using the FDA Adverse Event Reporting System - Tu, Jiakuan; Zhang, Chaoxiang; Xie, Shuihua; He, Jianhua; Zhang, Hao (Frontiers in Medicine, 2025)
BackgroundCyclobenzaprine, a centrally-acting muscle relaxant, is widely used for the treatment of musculoskeletal pain. Despite its efficacy, concerns regarding its safety profile, particularly adverse events (AEs), have been increasingly reported. This study aims to comprehensively analyze cyclobenzaprine-related AEs using the FDA Adverse Event Reporting System (FAERS) database to identify potential safety signals and inform clinical practice.MethodsA retrospective pharmacovigilance study was conducted using FAERS data from Q1 2004 to Q3 2024. Reports involving cyclobenzaprine as the primary suspect drug were analyzed. Descriptive statistics and disproportionality analyzes, including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multinomial Gamma Poisson Shrinkage (MGPS), were employed to detect safety signals. Subgroup analyzes were performed to explore demographic heterogeneity. Furthermore, the Weibull distribution was utilized to construct a model for the risk of adverse events as time progresses.ResultsOut of 18,289,374 AE reports, 2,425 were linked to cyclobenzaprine. Employing four distinct computational approaches at the preferred term (PT) level, we pinpointed 1,100 PTs signifying remarkable adverse reactions. The adverse reactions listed on the drug’s label, like cardiac arrest, respiratory arrest, drug hypersensitivity, dizziness, and somnolence, presented conspicuous signals. In addition, we discovered potential adverse reactions not detailed on the label, for example, toxicity to various agents, completed suicide, drug abuse, overdose, drug interaction, and confusional state. Subgroup analysis brought to light gender—specific AEs. Males had a higher likelihood of experiencing delirium and hallucinations, whereas females were more inclined to encounter drug hypersensitivity and muscle spasms. The vast majority of these AEs were reported during the first month of cyclobenzaprine treatment, with a median onset time of 7 days.ConclusionThis study confirms known AEs associated with cyclobenzaprine and identifies new potential risks, such as toxicity and suicidal behavior. These findings underscore the need for enhanced monitoring and further research to mitigate risks, particularly in vulnerable populations. Clinicians should remain vigilant for both somatic and psychiatric AEs when prescribing cyclobenzaprine, especially in patients with a history of mental health issues or substance abuse.